2017
DOI: 10.1038/s41598-017-06726-7
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor (GCSF) fused with Fc Domain produced from E. coli is less effective than Polyethylene Glycol-conjugated GCSF

Abstract: Human granulocyte colony-stimulating factor (GCSF) is a well-known cytokine for neutropenia treatment. However, daily injections are required due to the short circulating half-life of the protein. To overcome this bottleneck, we fused GCSF with the Fc domain of IgG1 at the C terminus (GCSF-Fc) and with the maltose binding protein (MBP) tag at the N-terminus and expressed it as a soluble protein in the cytoplasm of E. coli. We also conjugated PEG aldehyde to GCSF to make PEG-GCSF. The bioactivities of GCSF-Fc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Studies have shown that single injections of PEG-rhG-CSF were at least as potent as multiple injections of rhG-CSF in treating neutropenia [42]. Fusion of rhG-CSF to an Fc receptor [43] or serum albumin [44,45] was effective in increasing half-life of rhG-CSF and thus mobilization efficiency. In all of these studies, plasma levels of rhG-CSF were considered to be a marker for effectiveness of the modification.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that single injections of PEG-rhG-CSF were at least as potent as multiple injections of rhG-CSF in treating neutropenia [42]. Fusion of rhG-CSF to an Fc receptor [43] or serum albumin [44,45] was effective in increasing half-life of rhG-CSF and thus mobilization efficiency. In all of these studies, plasma levels of rhG-CSF were considered to be a marker for effectiveness of the modification.…”
Section: Discussionmentioning
confidence: 99%
“…103 Choe and coworkers group attempted to address this issue through conjugation 20kDa PEG to the amine terminus of G-CSF. 104 The in vitro activity and the half maximal effective concentration (EC 50 ) of the conjugate and native protein samples were investigated through the incubation of mouse myelogenous leukemia cells which ultimately showed similar activity suggesting pegylation does not negatively impact biological activity of G-CSF. The in vivo activity was determined via the injection of the native and conjugated protein into neutropenic rats (Fig 8).…”
Section: Recombinant Human Interferon-alpha (Ifn-α)-mentioning
confidence: 99%
“…In the case of antibody fragments, PEGylation has been shown to lengthen their circulating half-life, enhance their proteolytic resistance of therapeutic proteins, and reduce their immunogenicity. 27,29,41 Various PEGylation strategies have been studied for different therapeutic proteins, such as nonspecific PEGylation, thiol and bridging PEGylation, enzymatic PEGylation, and noncovalent PEGylation, 23,27…”
Section: Peg-s-fab Induces More Potent In Vivo Antitumor Activitymentioning
confidence: 99%